2009
DOI: 10.1021/ol901065e
|View full text |Cite
|
Sign up to set email alerts
|

Hetero-Diels−Alder Reactions of Cyclic Ketone Derived Enamide. A New and Efficient Concept for the Asymmetric Robinson Annulation

Abstract: Chiral enamides, easily prepared in one step from a cyclic ketone and an oxazolidinone, are successfully employed in high-yielding, endo, and facially selective Hetero-Diels-Alder reactions involving activated oxadienes and Siever's reagent as catalyst. From the resulting bicyclic heteroadducts, a novel and efficient asymmetric modification for the Robinson annulation of cyclic monoketones is described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 27 publications
0
21
0
2
Order By: Relevance
“…[185] The acid-catalyzed reaction of the chiral oxazolidinone with a cyclic ketone furnishes the desired dienophile 312 which can react with an alkyl arylidene-pyruvate (311) under Eu(fod) 3 catalysis to yield the desired adduct (313) in high yields (>82 %) with a good endo/exo selectivity (usually >90:10) and with almost complete facial selectivity. After total reduction of the methyl ester group (314), acidic treatment leads to the formation a mixture of REVIEW octalone 316 and 1,5-diketone 315 (which can further be cyclized in the classical conditions).…”
Section: Reviewmentioning
confidence: 99%
“…[185] The acid-catalyzed reaction of the chiral oxazolidinone with a cyclic ketone furnishes the desired dienophile 312 which can react with an alkyl arylidene-pyruvate (311) under Eu(fod) 3 catalysis to yield the desired adduct (313) in high yields (>82 %) with a good endo/exo selectivity (usually >90:10) and with almost complete facial selectivity. After total reduction of the methyl ester group (314), acidic treatment leads to the formation a mixture of REVIEW octalone 316 and 1,5-diketone 315 (which can further be cyclized in the classical conditions).…”
Section: Reviewmentioning
confidence: 99%
“…14 The pyrrole dicarboxaldehyde 9 15, 16 was then coupled under biphasic conditions 17 to afford the key pyrrologlycal 10 .…”
mentioning
confidence: 99%
“…While Cu(SbF 6 ) 2 , Sc(OTf) 3 , and Eu(fod) 3 yielded only the aldol product 20a, the desired HDA product 19a was obtained using La(OTf) 3 , Yb(OTf) 3 , and Y(OTf) 3 . In contrast to the IED-HDA reactions of enamide derived from cyclohexanone, which required refluxing temperature, 8 these reactions were conducted either at room temperature or at 4°C. Solvents were found to play a key role in determining the chemoselectivity.…”
Section: Scheme 5 Direct Asymmetric Aldol Reactions Catalyzed By Enammentioning
confidence: 99%
“…5e Recently, Gallier and coworkers have reported that chiral enamides derived from cyclic ketones can also serve as a dienophile in Eu(fod) 3 catalyzed IED-HDA reactions. 8 The rapid growth of organocatalysis in the last decade has significantly changed the profile of asymmetric catalysis. The first organocatalytic version of the IED-HDA reaction was made possible by the Jorgenson group in 2003.…”
mentioning
confidence: 99%